2009
DOI: 10.1063/1.3213076
|View full text |Cite
|
Sign up to set email alerts
|

Retroreflecting polarization spectroscopy enabling miniaturization

Abstract: We describe and characterize alternative configurations for Doppler-free polarization spectroscopy. The suggested apparatus enables complete pump/probe beam overlap and allows substantial miniaturization. Its utility and performance for narrow linewidth, high-stability frequency locking is discussed for the /5S(1/2)F=2>-->/5P(3/2)F(')>D(2) transition in (87)Rb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…While the increased signal strength of the cycling resonance is the most striking attribute of the POLEAS method, there are other appealing aspects that could prove equally beneficial. The simplicity of the experimental configuration and the fact that the Doppler background is automatically removed without the need for a separate beam (as in D-F SAS), mean that POLEAS can readily be implemented in a compact package [22]. Furthermore, by enhancing the cycling transition signal and simultaneously reducing the other nearby spectral features, an auto-locking laser stabilization scheme becomes easier to accomplish, especially compared with D-F SAS, where the crossover peaks provide the strongest features.…”
Section: Resultsmentioning
confidence: 99%
“…While the increased signal strength of the cycling resonance is the most striking attribute of the POLEAS method, there are other appealing aspects that could prove equally beneficial. The simplicity of the experimental configuration and the fact that the Doppler background is automatically removed without the need for a separate beam (as in D-F SAS), mean that POLEAS can readily be implemented in a compact package [22]. Furthermore, by enhancing the cycling transition signal and simultaneously reducing the other nearby spectral features, an auto-locking laser stabilization scheme becomes easier to accomplish, especially compared with D-F SAS, where the crossover peaks provide the strongest features.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, a weak linearly polarized probe beam is superimposed on a circularly polarized counter-propagating pump beam in a gas or vapor cell. [26][27][28][29] The observed signal is derived from the change in the polarization of the probe laser beam after it traverses the gas. This change is due to the optical anisotropy induced by the stronger pump beam, which arises from optical pumping that redistributes the population of the magnetic sublevels.…”
Section: B Polarization Spectroscopymentioning
confidence: 99%
“…Some compact [4] or miniaturized setups [5][6][7] have been proposed to stabilize a laser source frequency using SA resonances. Inspired by the work of Villalba et al [8], who observed SA resonances on an atomic vapor probed by diffuse light, we consider in this work the possibility of using diffuse light in a SA setup and we identify some advantages for its miniaturization.…”
mentioning
confidence: 99%